EFFECTIVENESS OF COMPLAINT HANDLING MOBILE APP BASED IN THE COMMUNICATION DEPARTMENT OF TANGERANG SELATAN CITY - Imam Chairudin; Izzatusholekha Izzatusholekha (Sean Institute, 2023)
The term Smart City is very popular among regional officials who are promoting sustainable development in areas managed by each regional head . One of them is the City of South Tangerang, which started this with a mobile application for public complaints inspired by the characteristics of a Smart City, namely Smart Mobility and Smart Living. Smart Mobility was appointed because people now live in the digital era, where they struggle with cellphones every day to access anything. Meanwhile, Smart Living, one of the characteristics of a Smart City, wants life to run safely and internally from any problems around it. The SIARAN mobile application carries these two issues so that every incident can be reported directly through the application. The SIARAN mobile application was deliberately created by the South Tangerang City Government to be able to analyze the management of government roads in South Tangerang City more effectively and efficiently in the hands of the community through a mobile application. Supporting concepts and theories in this research are communication, development communication, public relations in the digital era, public relations communication models, government public relations, publications, outreach, Smart City, and digital applications. The purpose of this research is to find out how to implement the